A cross-layer design for congestion control in UWB-based wireless sensor networks. (5th August 2009) - Pilakkat, Reena; Jacob, Lillykutty
In this paper a cross-layer design for congestion control is proposed for wireless sensor networks (WSNs). The multiple access communication for the WSNs is assumed to be Ultra-Wide Bandwidth (UWB) Time-Hopping Spread-Spectrum (TH-SS) impulse radio. Joint congestion and power control is proposed and formulated as a network utility maximisation problem, which is then solved by distributed iterative algorithms for flow rate adaptation and power adaptation on every link. Power control algorithm allocates the right amount of power at the right nodes to alleviate the bandwidth bottlenecks, while maintaining the signal to interference-and-noise ratio above a given threshold for every link. Fluid flow simulations show that considerable improvement in throughput can be obtained while also transmitting at lower power levels. A comparative study of the performance of hop-by-hop and end-to-end congestion control mechanisms is also made. Hop-by-hop approach offers significant reduction in the buffer size requirement, under high feedback delays.